2014
DOI: 10.3390/md12074247
|View full text |Cite
|
Sign up to set email alerts
|

Dolabelladienols A–C, New Diterpenes Isolated from Brazilian Brown Alga Dictyota pfaffii

Abstract: The marine brown alga Dictyota pfaffii from Atol das Rocas, in Northeast Brazil is a rich source of dolabellane diterpene, which has the potential to be used in future antiviral drugs by inhibiting reverse transcriptase (RT) of HIV-1. Reexamination of the minor diterpene constituents yielded three new dolabellane diterpenes, (1R*,2E,4R*,7S,10S*,11S*,12R*)10,18-diacetoxy-7-hydroxy-2,8(17)-dolabelladiene (1), (1R*,2E,4R*,7R*,10S*,11S*,12R*)10,18-diacetoxy-7-hydroxy-2,8(17)-dolabelladiene (2), (1R*,2E,4R*,8E,10S*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Error bars represent standard deviation cilliolata, was also tested for its anticancer potential in different cell lines including MCF-7 (Caamal-Fuentes et al 2014) and in this study, the extract was effective only at microgram per mL concentrations. Furthermore in several studies focusing on the anti-cancer potential of pure compounds isolated from Dictyota species in different cell lines including MCF-7, IC 50 values calculated for all of the compounds were at microgram per mL scale (Jongaramruong and Kongkam 2007;Ayyad et al 2011;Abou-El-Wafa et al 2013;Pardo-Vargas et al 2014). Since our extract was much more effective compared to all counterparts and to all pure compounds mentioned, we believe either the extract itself or the active compounds of the extract have a strong potential to be used as anti-cancer agent.…”
Section: Discussionmentioning
confidence: 99%
“…Error bars represent standard deviation cilliolata, was also tested for its anticancer potential in different cell lines including MCF-7 (Caamal-Fuentes et al 2014) and in this study, the extract was effective only at microgram per mL concentrations. Furthermore in several studies focusing on the anti-cancer potential of pure compounds isolated from Dictyota species in different cell lines including MCF-7, IC 50 values calculated for all of the compounds were at microgram per mL scale (Jongaramruong and Kongkam 2007;Ayyad et al 2011;Abou-El-Wafa et al 2013;Pardo-Vargas et al 2014). Since our extract was much more effective compared to all counterparts and to all pure compounds mentioned, we believe either the extract itself or the active compounds of the extract have a strong potential to be used as anti-cancer agent.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, three different isomers of 2,6‐dolabelladiene and three of 2,8(17)‐dolabelladiene were isolated from the brown alga Dictyota pfaffii and exhibited anti‐​HIV‐​1 activity. Dolabelladienetriol showed strong inhibitory activity against HIV‐1 reverse transcriptase enzyme and was thus deemed as a potential drug for antiretroviral therapy . Pardo‐Vargas et al .…”
Section: Resultsmentioning
confidence: 99%
“…The antiviral data showed that they exhibited low antiHIV-1 activity and low toxicity. Supported by the fact that oxygenated dolabellanes, isolated from brown algae, showed good antiviral activity [27,28], the authors of this article obtained derivatives 16-18 by epoxidation, by epoxide opening and by allylic oxidation, respectively. These oxygenated compounds showed significant improvement in the antiHIV-1 potency (100-fold) [29].…”
Section: Eunicea Laciniatamentioning
confidence: 98%